Implementation of the Principle of Business Judgement Rule Doctrine to State-Owned Companies as an Effort to Protect Directors in Good Faith - I Made Pria Dharsana; Indrasari Kresnadjaja; I Putu Lingga Dhananjaya (Faculty of Law, Universitas Pekalongan, 2023)
The Business Judgement Rule is a doctrine that protects Directors in good faith for the Company's losses. The point is that as long as the Board of Directors acts in good faith and solely for the Company's benefit. However, it turns out that the Company still suffers losses. It does not necessarily become the burden of the Board of Directors personal responsibility. Therefore, the Board of Directors cannot be held responsible for the Company's losses if the Board of Directors, in carrying out actions, has fulfilled all its obligations with the principles of good corporate Governance (GCG). If all GCG obligations and principles have been fulfilled, the Board of Directors is categorized as having good faith and cannot be declared wrong. The results of the author's study, in the context of the Business Judgment Rule Doctrine, the losses incurred are normal or reasonable business losses, and therefore the Company is responsible. And no one can be punished if there is no mistake. With the background of the Constitutional Court Decision Number 01/PHPUPres/XVII/2019 (Constitutional Court Decision 01) and two Supreme Court Decisions, the author tries to examine in more detail related to Decision No. 3849/K/Pid.Sus/2019 dated December 2, 2019, on behalf of Defendant Frederick ST Siahaan (former Finance Director of Pertamina) / (Supreme Court Decision 3849) and Decision No. 121K/Pid.Sus/2020 dated March 9, 2020, on behalf of Defendant Karen Agustiawan (former President Director of Pertamina).